(untitled) (Scottish Historical and Archaeological Internet Reports, 2005)
An account of the methodology employed is followed by a detailed archaeological description of the excavated section. It is acknowledged that the identification of six main archaeological horizons is a simplification of the stratigraphy. Features included two middens, a hearth and possible stone structural elements. A radiocarbon date of 780-1120 AD at 2 sigma confidence was obtained from the hearth. There was certainly evidence for earlier activity and the possibility of continuity into the medieval period.